Can Engaged and Positive Employees Delight Customers?. Issue 1 (February 2018) - Shaheen, Musarrat; Zeba, Farrah; Mohanty, Pankaj Kumar
The Problem: Although there have been a plethora of studies on the determinants of customer delight in marketing literature, less attention has been given to understand the role of employees' work engagement and psychological capital (PsyCap) in satisfying and delighting customers. The objective of the present study is threefold—the first is to examine how engaged employees are positive and efficacious; the second is to investigate how engaged, positive, and efficacious employees delight patients specifically in the health care sector; and the third is to examine how the relationship between employees' positive PsyCap and customer delight is mediated by beneficiary contact, which is the perception of employees about the meaningful impact of their efforts on their patients. The Solution: Previous studies have shown that employees who are absorbed, dedicated, and immersed in their work are more confident and positive at their workplace. Engaged, positive, and confident employees not only keep themselves but also their customers happy and positive through their optimistic outlook and efficacious work behavior. Responses are collected from 200 employees and their 200 patients from different hospitals of India. Hierarchical regression analysis shows a significant and positive relationship between work engagement, PsyCap, and customer delight. Work engagement is found to predict PsyCap and customer delight. Beneficiary contact is found to mediate between the relationship of PsyCap and customer delight. The originality of the article lies in its interdisciplinary approach to understand how engaged and dedicated employees keep themselves and their patients positive and delighted. The Stakeholders: This study is of relevance to human resource development (HRD) professionals, customer relationship managers of the health care sector, and also academicians belonging to the disciplines of marketing and human resource management. The findings of this study would help them understand how engaged employees lead to employees' positive PsyCap and customer delight. Furthermore, they will also understand the vital role of the interface between employees and customers, as beneficiary contact mediates the relationship of employees' PsyCap and customer delight.